Pertanggungjawaban Korban Tindak Pidana Perdagangan Orang yang Menjadi Pelaku Tindak Pidana Narkotika - Taris Luthfansyah (Faculty of Law, Universitas Airlangga, 2022)
AbstractThe phenomenon of globalization creates many serious crime problems, one of which is the crime of trafficking in persons. The crime of trafficking in persons is a contemporary slavery and violation of human rights. The crime of trafficking in persons is closely related to narcotics crimes, this can be seen in the free circulation of narcotics Victims of trafficking in persons are exploited to distribute narcotics to various regions and countries. Narcotics dealers use victims of trafficking in persons to be free from punishment in the event of an arrest in the delivery of the narcotics. That way the victims of the crime of trafficking in persons will receive the legal consequences of their actions. Whereas in Article 18 of Law No. 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons, it is stated that victims of the crime of trafficking in persons cannot be punished.Keywords: Human Trafficking; Narcotics; Article 18 of the PTPPO Law. AbstrakFenomena globalisasi membuat banyak permasalahan kejahatan yang cukup serius, salah satunya adalah tindak pidana perdagangan orang. Tindak pidana perdagangan orang merupakan perbudakan masa kini dan pelanggaran hak asasi manusia. Tindak pidana perdagangan orang sangat berkaitan dengan tindak pidana narkotika, hal tersebut dapat dilihat pada peredaran bebas narkotika. Pelaku bandar narkotika menggunakan tindak pidana perdagangan orang untuk mengedarkan narkotika. Para korban tindak pidana perdagangan orang dieksploitasi unutuk mendistribusikan narkotika ke berbagai daerah dan negara. Pelaku bandar narkotika menggunakan korban tindak pidana perdagangan orang agar terbebas dari hukuman apabila terjadi penangkapan dalam pengiriman narkotika tersebut. Dengan begitu para korban tindak pidana perdagangan orang yang akan menerima akibat hukum dari perbuatanya. Padahal dalam pasal 18 Undang-Undang No.21 Tahun 2007 tentang Pemberantasan Tindak Pidana Perdagangan Orang menyebutkan bahwa korban dari tindak pidana perdagangan orang tidak dapat dipidana.Kata Kunci: Perdagangan Orang; Narkotika; Pasal 18 UU PTPPO.